Thoracic Duct Embolization for Postoperative Lymphatic Fistula - Ayhan Erdemir; Murat Dökdök; Kemal Raşa (Case Reports in Surgery)
Lymphatic fistula as a rare entity particularly emerges after head and neck cancer surgery. It may lead to delayed wound healing, electrolyte loss, malnutrition, dehydration, and immune suppression. Therefore, rapid diagnosis and treatment are of the utmost importance. We aimed to present a lymphatic fistula case who was treated successfully by lymphangiography with percutaneous embolization of the thoracic duct. We believe that minimally invasive techniques could be an alternative to the conservative approach as the first-line choice.